Freedom, warriors’ bond, legal book. The Lex Salica between Barbarian custom and Roman law - Jean-Pierre Poly (Clio@Themis, 2021)
Salic Law, the most famous of the so-called barbarian leges, was both barbarian and roman. It was made during the 4th century for the Frankish military dependants (dediticii) and their families settled in the Extrema Galliae, the Far Gaul. Its main goal was to eradicate the feud system, unacceptable in the Roman army. It did not succeed in the long run but it gave the Franks the cohesion which allowed them to conquer Gaul, the text turning ultimately into an element of national identity down to the French revolution.